2012
DOI: 10.1111/j.1439-0523.2011.01892.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of microsatellite regions across legume genera enhances marker repertoire and genetic diversity study in Phaseolus genotypes

Abstract: To study the conservation of microsatellite regions, a set of 137 microsatellite markers developed from Phaseolus, Cajanus, Lens and Cicer genera of Leguminosae family were tested for their transferability across 16 genotypes of Phaseolus belonging to diverse collections from South America and Asia. Considerable transferability was observed with markers derived from Cajanus (60%), Lens (46%) and Cicer (28%). Of the total 122 loci were amplified, 82 cross-species polymorphic amplicons were obtained. Maximum num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
(25 reference statements)
1
9
0
Order By: Relevance
“…nigra and V. grandiflora. Average transferability of SSR markers was 56.25% which was in concordance with the previously published results on legumes (Reddy et al 2010, Datta et al 2012, Gupta et al 2013). Figure 2), with exception of Vicia narbonensis and Vicia faba, which had the same banding pattern with primer (GA)8T (Table 4).…”
Section: Resultssupporting
confidence: 81%
“…nigra and V. grandiflora. Average transferability of SSR markers was 56.25% which was in concordance with the previously published results on legumes (Reddy et al 2010, Datta et al 2012, Gupta et al 2013). Figure 2), with exception of Vicia narbonensis and Vicia faba, which had the same banding pattern with primer (GA)8T (Table 4).…”
Section: Resultssupporting
confidence: 81%
“…Thus there is a need to screen and identify polymorphic SSR markers in greater numbers to facilitate analyses of genetic diversity in mungbean. The process may include transferring the SSR markers from other closely related legumes such as moth bean, adzuki bean, cowpea and rice bean as this will also facilitate correlated studies in across related crops (Datta et al 2013;Jingade et al 2014;Shivakumar et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…(Gupta et al, 2012) have reported 92 per cent transferability of greengram SSR markers, 91 per cent of adjuki bean SSR markers and 86 per cent of cowpea SSR markers to black gram. (Datta et al, 2013) reported highest transferability of SSR markers from common bean followed by lentil, field pea and chickpea to pigeonpea. (Agbagwa et al, 2015) reported successful transferability of SSR markers from Vigna savi to pigeonpea.…”
Section: Transferability Of Ssr Markersmentioning
confidence: 99%
“…The estimates of PIC of transferable SSR markers from Vigna savi to cultivated and wild relatives of Cajanus adams ranged from 0.24 to 0.69 with an average of 0.47 (Agbagwa et al, 2015). Datta et al, (2013) reported a fairly high estimates of PIC (ranging from 0.5 to 0.6) of cross transferable SSR markers from common bean, lentil, field pea and chickpea to pigeonpea. The reported significant differences in quantitative traits means of 14 ABL were amply reflected at transferable SSR marker allelic diversity in the present study.…”
Section: Population Genetic Parametersmentioning
confidence: 99%